Mixed-Criticality Real-Time Scheduling for Multicore Systems - Mollison, Malcolm S; Erickson, Jeremy P; Anderson, James H; Baruah, Sanjoy K; Scoredos, John A (2010 IEEE 10th International Conference on Computer and Information Technology, 2010)
Current hard real-time scheduling and analysis techniques are unable to efficiently utilize the computational bandwidth provided by multicore platforms. This is due to the large gap between worst-case execution time predictions used in schedulability analysis and actual execution times seen in practice. In this paper, we view this gap as "slack'' that can be accounted for during schedulability analysis and reclaimed for less critical work. We use this technique to develop an architecture for scheduling mixed criticality real-time workloads on multiprocessor platforms. Our architecture provides temporal isolation among tasks of different criticalities while allowing slack to be redistributed across criticality levels.